Westward Ho : expanding global role for China's navy - Koh, Collin Swee Lean (2014)
China has recently deployed a frigate in support of multinational efforts to dismantle and dispose of Syrian chemical weapons. Will this herald an expanding global role for the People’s Liberation Army Navy?